Icebreaking Ensuring Year-Round Regular Navigation on Routes of the Northen Sea Route - Mikhail Aleksandrovich Zagorodnikov (Управленческое консультирование)
For ensuring year-roundregular navigation on routes NSR innovative ice breakers with the increased icebreaking capability and speed of the movement in an ice field of a certain thickness are under construction and designed. The increase in functional characteristics of ice breakers led to increase of cost of their construction. In article the method of distribution of ice breakers on routes NSR allowing with maximum to use efficiency their functional charac teristics is considered.